2006
DOI: 10.1007/s10681-006-9225-1
|View full text |Cite
|
Sign up to set email alerts
|

Pollen–pistil interaction in the inter-specific crosses of Sesamum sp

Abstract: The wild species of Sesamum have long been recognized as an important source of many valuable pest and disease resistance genes and other novel traits such as male sterility and plant type for the cultivated taxon. Utilization of these species in crop improvement is marginal because of their inherent low crossability with the cultigen. An understanding of the biological nature of incompatibility systems that impede hybridization offers tools for successful introgressions into cultivated sesame. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…In addition, although some pollen grains appeared to overcome this barrier and ultimately germinated on stigmas at 8 h after pollination, most of pollen tubes revealed abnormalities like branching, coiling, convolutions and curving of tips. This phenomenon has been reported in interspecific crosses of other plants (Heslop-Harrison 2000; Ram et al 2006Ram et al , 2008. Thus, it is speculated that the interaction between some chemical products secreting from stigmas and those secreting from pollen walls was incompatible, and consequently prevented pollen grains from germinating normally in the cross between D. grandiflorum 'Yuhuaxingchen' and D. nankingense.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, although some pollen grains appeared to overcome this barrier and ultimately germinated on stigmas at 8 h after pollination, most of pollen tubes revealed abnormalities like branching, coiling, convolutions and curving of tips. This phenomenon has been reported in interspecific crosses of other plants (Heslop-Harrison 2000; Ram et al 2006Ram et al , 2008. Thus, it is speculated that the interaction between some chemical products secreting from stigmas and those secreting from pollen walls was incompatible, and consequently prevented pollen grains from germinating normally in the cross between D. grandiflorum 'Yuhuaxingchen' and D. nankingense.…”
Section: Discussionsupporting
confidence: 65%
“…Pollination is the primary step in seed set, and events starting at pollination and terminating at fertilization in wide crosses involve complex and harmonious interactions including cell-cell recognition and cellular signaling (Mascarenhas 1993;Wilhelmi and Preuss 1997;Malhó 1998;Franklin-Tong 1999;de Graaf et al 2001). Failures in pollination are thought to be widespread in plants and a common cause of low seed set (Wilcock and Neiland 2002;Marta et al 2004;Pellegrino et al 2005;Hodnett et al 2005;Ram et al 2006;Lee et al 2008;Spielman and Scott 2008). For instance, Mazzucato et al (2003) indicated that a defective pollen-pistil interaction was a main factor leading to low seed set in the parthenocarpic fruit tomato mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Sesame production in India is encouraging, as more than 30 % of world production of sesame is contributed by India alone and India ranks top in total production. Despite being largely self-sufficient in production, sesame productivity is in decline (Anthony et al 2015;FAOSTAT 2015) and it is of great concern and that is caused mainly due to unavailability of high yielding varieties (Duhoon 2004;Ram et al 2006). Sesame is considered as a nutritious oilseed crop being rich source of protein (18-25 %), carbohydrate (13.5 %), minerals and healthy polyunsaturated fatty acid (Bedigian et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…If pollen tubes at the ovule micropyle can be presumed to indicate fertilization (Chaix and Marchais 1996;Ram et al 2007), then a post-fertilization reproductive barrier is the most likely mechanism isolating P. fimbriata from P. purshii. The reproductive isolation for these species showed no evidence of a pre-zygotic barrier such as earlier acting pollen-pistil incompatibilities that prevent hybridization in other taxonomic groups (Ram et al 2006;Ram et al 2007).…”
Section: ]mentioning
confidence: 89%